2022
DOI: 10.4081/pmc.2022.279
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of large scalp infantile hemangioma in 30-month-old infant

Abstract: Infantile Hemangiomas (IH) are the most common benign tumor of infancy, occurring in over 10% of newborns. The head and neck is the most frequently affected area (60%), and the scalp is a typical site for such large lesions. Scalp-IHs are usually focal lesions that can be both disfiguring and may lead to complications such as ulceration and bleeding. We describe a case of a 30-months old female who presented a large scalp-IH at birth that rapidly grew in the first year of life. Topical and systemic treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Although excision of IH presents the risk of bleeding due to the vascularity of the tumor, it may be necessary if the lesion is refractory to pharmacological treatment or causing life-threatening sequelae: recurrent bleeding, ulceration, congestive heart failure, or obstruction of a vital structure (airway, ear canal, and visual axis) 7,30 . Indications for surgical intervention of the scalp lesions in our review varied: 32% of patients exhibited critical anatomic disruption (4 ears, 2 eyes), 8,11,13,15 32% had ulceration or erosion, 9,11–14 16% with cardiac involvement, 8,10,15 11% with increased bleeding, 11,18 and 26% due to rapid growth or unresponsiveness to prior therapies 11,12,16,17 . Notably, excision was performed significantly earlier in patients with signs of cardiac involvement (<1 month) 8,10,15 …”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Although excision of IH presents the risk of bleeding due to the vascularity of the tumor, it may be necessary if the lesion is refractory to pharmacological treatment or causing life-threatening sequelae: recurrent bleeding, ulceration, congestive heart failure, or obstruction of a vital structure (airway, ear canal, and visual axis) 7,30 . Indications for surgical intervention of the scalp lesions in our review varied: 32% of patients exhibited critical anatomic disruption (4 ears, 2 eyes), 8,11,13,15 32% had ulceration or erosion, 9,11–14 16% with cardiac involvement, 8,10,15 11% with increased bleeding, 11,18 and 26% due to rapid growth or unresponsiveness to prior therapies 11,12,16,17 . Notably, excision was performed significantly earlier in patients with signs of cardiac involvement (<1 month) 8,10,15 …”
Section: Discussionmentioning
confidence: 92%
“…Review of the literature revealed 19 previously published case studies (from 1981 to 2022) of pediatric scalp hemangiomas undergoing excision (Supplemental Table 1, Supplemental Digital Content 1, http://links.lww.com/SCS/F594). [8][9][10][11][12][13][14][15][16][17][18] Of the patients whose sex was reported, the majority (78%) were female (F:M ratio of 3.5). Patient age at the time of excision ranged from 2 days old to 14 years old, with a median age of 16 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations